Legal Protection of Participants of the Regional Contribution Assistance Social Security Agency in Choosing A First-Level Health Facility - Hidayah, Nurul; Huda, Mokhamad Khoirul; Pramono, Agung (Journal of Language and Health, 2024)
In order to guarantee that all citizens, notably individuals who have enrolled in national health insurance, are capable of getting medical care without any barriers, national health insurance is necessary. This research indicates to analyze the legal safeguards provided for individuals that are part of the national health insurance program whenever choosing first level health facilities. This study combines a normative and empirical approach for examining the laws and regulations controlling the legal entitlements of national health insurance participants, as well as their implementation in practice. Legal materials for this study were collected from books, magazines, articles, papers, journals, newspapers, and works by legal experts to obtain relevant secondary legal data. The findings are presented systematically, linking the materials to address the research problem comprehensively. In the analysis phase, which is crucial for the study, the collected data is processed and interpreted to uncover truths that answer the research questions. The legal material was analyzed qualitatively using descriptive-analytical methods. This approach relates the identified issues to literature, expert opinions, and applicable legal regulations. The outcomes of the research reveal that, despite legal regulations granting national health insurance participants the opportunity to choose first-level health care facilities, this right is still violated. The key hurdles include the limited number of first-level health facilities that partner with national health insurance, unequal distribution of health facilities, and a lack of socialization from national health insurance. The research presented here suggests raising socialization about national health insurance participants' rights since deciding on first level healthcare facilities, raising the number of joining forces primary level with health facilities, and more rigorous oversight of participant rights implementation. With these efforts, it is envisaged that the rights of national health insurance participants to choose first level health facilities may be properly preserved and enable expanded access and quality of health services in Indonesia.